THE CHANGING FACE OF ACUTE NEUROLOGY: EXPERIENCE FROM TWO DECADES OF THE CAMBRIDGE NEUROLOGY EMERGENCY CLINIC. Issue 11 (14th October 2015) - Axinte, Laura; Sawcer, Stephen; Stacpoole, Sybil
Abstract : Acute neurological presentations are a common problem, accounting for around 17% of GP consultations, 10% of A&E visits and around 20% of the medical take. There is an increasing appreciation of the need to reconfigure neurological services to meet this need, but the challenge is to provide a service for those who most need it with an under-resourced specialty. The Royal College of Physicians 2012 Consultant Physician Survey reported that there were 716 neurology consultants in the UK, resulting in 1 per 90, 000 population, significantly lower than the recommended RCP minimum of 1 consultant per 70, 000, every day of the week. One solution to the evident need is providing rapid access ambulatory pathways. Here we report on the Cambridge experience of nearly two decades provision of an emergency neurology clinic at Addenbrooke's Hospital. We show how the service has evolved and the changing patterns of presentation, management and outcomes of the patients seen. Annualised attendance data demonstrates increasing demand, whilst the proportion of patients presenting with headaches (now 40%) has escalated dramatically. By contrast, the number of patients referred with problems related to established chronic neurological diseases has fallen considerably, no doubt related to the development of specialist nurses and clinics.